Synthetic cannabinoid receptor agonists (scras) induced seizure: a case report - Altıntaş, Merih; Kuru, Murat (Journal of Dependence, 2016)
With an ever-increasing prevalence, exposing new challenges to healthcare personnel, the use of synthetic cannabinoid receptor agonists (SCRAs) affects many systems. Clinical manifestations that may be caused by it become more predictable day by day thanks to increasing number of case reports on this issue. The use of these substances gives rise to serious side effects, which in turn affect psychiatric, neurological, cardiovascular, renal and pulmonary systems. Recently, there are a growing number of reports indicating that SCRAs would lead to seizures. It is considered that notably the patients referred to emergency rooms due to SCRA induced toxicity may be experiencing a series of life-threatening clinical presentations, one of which would probably be seizure, and which may sometimes require intensive care followup. This shows that all clinicians and the society should be highly aware of and get prepared for potential hazards to be triggered by use of SCRAs. This report makes mention of a case where a patient without any record of seizure in his medical history, who experienced his first epileptic seizure following SCRAs induced intoxication, and where the seizure was hardly terminated.